Modeling for ELMs and H-mode pedestal transport: MHD, gyrokinetic, neoclassical and integrated simulations - N. Aiba (Nuclear Fusion, 2025)
This paper provides a comprehensive review of recent advances in modeling and simulation studies investigating edge localized modes (ELMs) and transport physics in edge pedestal of tokamak plasmas. Following an overview of H-mode characteristics, including ELMy and ELM-free regimes, ELM control techniques, and pedestal transport physics, this review focuses on three key areas: advancements in linear and nonlinear MHD simulations to improve understanding ELM physics and access the effectiveness of ELM control techniques; progress in understanding of transport physics of both bulk and impurity plasmas in the edge pedestal, analyzed using gyrokinetic and neoclassical simulations; and the development of predictive models for H-mode pedestal profiles. Notably, the maturity of these approaches now enables meaningful validation through experimental comparisons, including the application of synthetic diagnostics. Building on these developments, this paper addresses critical simulation and modeling challenges that must be resolved to successfully predict robust operation scenarios for ITER and future fusion reactors, aiming to achieve high plasma performance while avoiding destructive transients such as ELMs.